2012
DOI: 10.1093/cvr/cvs134
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AMPK signalling by doxorubicin: at the crossroads of the cardiac responses to energetic, oxidative, and genotoxic stress

Abstract: Our results suggest that in the doxorubicin-challenged heart, a combined energetic, oxidative, and genotoxic stress elicits a specific, hierarchical response where AMPK is inhibited at least partially by the known negative cross-talk with Akt and MAPK pathways, largely triggered by DNA damage signalling. Although such signalling can be protective, e.g. by limiting apoptosis, it primarily induces a negative feedback that increases cellular energy deficits, and via activation of mTOR signalling, it also contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 53 publications
12
84
1
2
Order By: Relevance
“…DOX affects the mTOR pathway through AMPK, Akt, and p53-dependent and -independent mechanisms (11,37). Moreover, the induction of physiological hypertrophy with exercise is mediated through IGF-I, Akt, and mTOR signaling (26).…”
Section: Sed+dox Ex+dox Ex Dox (-) (+) (-) (+) (-) (+) (-) (+) (-) (+mentioning
confidence: 99%
See 1 more Smart Citation
“…DOX affects the mTOR pathway through AMPK, Akt, and p53-dependent and -independent mechanisms (11,37). Moreover, the induction of physiological hypertrophy with exercise is mediated through IGF-I, Akt, and mTOR signaling (26).…”
Section: Sed+dox Ex+dox Ex Dox (-) (+) (-) (+) (-) (+) (-) (+) (-) (+mentioning
confidence: 99%
“…Although exercise training has previously been shown to increase Akt phosphorylation (3), the role of Akt in DOX cardiotoxicity is less clear. While some studies have shown DOX decreases Akt phosphorylation, others have observed elevated Akt activity in vivo (6,11,25). Because many factors influence Akt phosphorylation, it appears the experimental model is very important for interpretation of Akt activity.…”
Section: Sed+dox Ex+dox Ex Dox (-) (+) (-) (+) (-) (+) (-) (+) (-) (+mentioning
confidence: 99%
“…10,11 Interestingly, mitochondrial alterations also seem to be involved in doxorubicin-mediated cardiotoxicity. 12,13 Moreover, alterations in energy signaling pathways, such as the AMP-activated protein kinase (AMPK), have been recently shown to be involved in doxorubicin cardiotoxicity, 12 but possible sex differences have not yet been evaluated.…”
mentioning
confidence: 99%
“…4 The inhibition of this signalling pathway causes cellular energy deficits. 5 Metformin on the other hand is currently one of the drugs used worldwide to treat diabetes mellitus type 2. It is known to be an insulin sensitizer and has a low potential to produce adverse effects especially in patients with underlying cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%